Literary Problems in the Book of Mormon involving 1 Corinthians 12, 13, and Other New Testament Books - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
The literary problem caused by the parallels between Moroni 7-10 and 1 Corinthians 12-13 can be explained if one realizes that Moroni had access to the same teachings of Christ as Paul, and that both received revelation, so that the Lord himself might be the author of both dissertations. Different prophets might have had similar inspiration in dealing with the same topics.